1794 : the city between the bridges : a novel - Natt och Dag, Niklas, 1979- (Atria Books, 2023)
In 1794 Stockholm, Jean Mickel Cardell, the one-armed watchman, investigates the death of Eric Three Roses' beautiful wife on their wedding night at the behest of the girl's mother, who is desperate for justice.